Treatment approaches in advanced penile cancer: targeted therapies and immunotherapy - Benjamin, David J.; Hsu, Robert C. (Frontiers in Oncology, 2025)
Penile cancer is a rare genitourinary malignancy which can be treated with surgery or radiation for localized disease, but often requires systemic treatment with chemotherapy for recurrent or metastatic disease. With the emergence of immune checkpoint inhibitors and targeted therapies for specific genomic aberrations in the treatment of over a dozen other cancers, recent studies have sought to identify therapies other than chemotherapy in treating this uncommon cancer. Several ongoing trials involving immune checkpoint inhibitors, tyrosine kinase inhibitors, and antibody drug conjugates are attempting to identify additional therapies.